2015
DOI: 10.1007/s12291-015-0515-z
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-Modulatory Effect and Therapeutic Potential of Brugia malayi Cystatin in Experimentally Induced Arthritis

Abstract: Helminths are known to modulate host's immune system and understanding this modulation can help in identification of novel therapeutic agents for autoimmune diseases. In this study, we have assessed the immune-modulatory activity and the therapeutic effect of Brugia malayi recombinant cystatin (rBmCys) in methylated BSA (mBSA) induced arthritis using rodent model. Administration of rBmCys has suppressed the severity of mBSA-arthritis in mastomys by reducing paw swelling and other clinical disease parameters as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The study of TGF-β in T-cell responses has shown differential results as an inhibitor or promoter of the inflammatory response. 11 In a recent study of patients with Sjögren's Syndrome and rheumatoid arthritis and a control group, it was concluded that TGF-β levels significantly decreased in rheumatoid arthritis patients. Researchers have also shown that TGF-β plays a role in fibrosis, which is often associated with inflammatory disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of TGF-β in T-cell responses has shown differential results as an inhibitor or promoter of the inflammatory response. 11 In a recent study of patients with Sjögren's Syndrome and rheumatoid arthritis and a control group, it was concluded that TGF-β levels significantly decreased in rheumatoid arthritis patients. Researchers have also shown that TGF-β plays a role in fibrosis, which is often associated with inflammatory disease.…”
Section: Discussionmentioning
confidence: 99%
“…8 Several studies on experimentally induced autoimmune disorders have shown that helminths or the products derived from them can alter the severity of allergy and autoimmune conditions via modulation of the host immune system, suppression of interferon gamma 10 Based on these studies, utilization of helminths or their products in the treatment of RA has been conceptualized. 11 The purpose of this study was to show that in rats experimentally infected with T canis significantly less joint inflammation was observed following intra-articular injection of Freund's complete adjuvant (FCA) in comparison with non-infected FCA-treated animals.…”
mentioning
confidence: 99%
“…This disease affects approximately 54.4 million (25%) people in the United States and is estimated to affect over 78 million by 2040 [ 109 ]. Several studies show that both preventive and therapeutic administration of B. malayi cystatin could suppress the severity of mBSA-induced arthritis [ 97 , 98 ]. Treated animals showed a reduction in paw swelling and a reduction in clinical disease parameters accompanied by a Th2 dominant immune response [ 97 , 98 ].…”
Section: Therapeutic Potential Of Parasite Cystatinsmentioning
confidence: 99%
“…Several studies show that both preventive and therapeutic administration of B. malayi cystatin could suppress the severity of mBSA-induced arthritis [ 97 , 98 ]. Treated animals showed a reduction in paw swelling and a reduction in clinical disease parameters accompanied by a Th2 dominant immune response [ 97 , 98 ]. Collagen-induced arthritis in DBA/1 mice was significantly attenuated following rSjCystatin treatment.…”
Section: Therapeutic Potential Of Parasite Cystatinsmentioning
confidence: 99%
See 1 more Smart Citation